Up-regulation of HER2 by gemcitabine enhances the antitumor effect of combined gemcitabine and trastuzumab emtansine treatment on pancreatic ductal adenocarcinoma cells. Issue 1 (December 2015) - Kan, Shin; Koido, Shigeo; Okamoto, Masato; Hayashi, Kazumi; Ito, Masaki; Kamata, Yuko; Komita, Hideo; Nagasaki, Eijiro; Homma, Sadamu
Abstract Background Although pancreatic ductal adenocarcinomas (PDAs) widely express HER2, the expression level is generally low. If HER2 expression in PDA cells could be enhanced by treatment with a given agent, then combination therapy with that agent and trastuzumab emtansine (T-DM1), a chemotherapeutic agent that is a conjugate of trastuzumab, might lead to significant antitumor effects against PDA. Methods Cell proliferation was examined by spectrophotometry. HER2 expression was examined by flow cytometry, immunoblot and quantitative reverse transcription polymerase chain reaction. T-DM1 binding to cells was examined by flow cytometry and enzyme-linked immunosorbent assay. Results Out of 5 tested human PDA cell lines, including MIA PaCa-2, three showed increases in HER2 expression after gemcitabine (GEM) treatment. The binding of T-DM1 to GEM-treated MIA PaCa-2 cells was higher than to untreated MIA PaCa-2 cells. Treatment with GEM and T-DM1 showed synergic cytotoxic effects on MIA PaCa-2 cellsin vitro . Cells in the G2M phase of the cell cycle were retained after GEM treatment and showed higher levels of HER2 expression, possibly contributing to the synergic effect of GEM and T-DM1. Conclusions Combined treatment with GEM and T-DM1 might confer a potent therapeutic modality against PDA as a result of GEM-mediated HER2 up-regulation.